Biosynthetically Guided Structure–Activity Relationship Studies of Merochlorin A, an Antibiotic Marine Natural Product. (23rd November 2017) - López‐Pérez, Borja; Pepper, Henry P.; Ma, Rong; Fawcett, Benjamin J.; Pehere, Ashok D.; Wei, Qi; Ji, Zengchun; Polyak, Steven W.; Dai, Huanqin; Song, Fuhang; Abell, Andrew D.; Zhang, Lixin; et al.
Abstract: The onset of new multidrug‐resistant strains of bacteria demands continuous development of antibacterial agents with new chemical scaffolds and mechanisms of action. We present the first structure–activity relationship (SAR) study of 16 derivatives of a structurally novel antibiotic merochlorin A that were designed using a biosynthetic blueprint. Our lead compounds are active against several Gram‐positive bacteria such as Staphylococcus aureus (SA), methicillin‐resistant Staphylococcus aureus (MRSA), vancomycin‐resistant Enterococcus faecium (VRE) and Bacillus subtilis, inhibit intracellular growth of Mycobacterium bovis, and are relatively nontoxic to human cell lines. Furthermore, derivative12 c {(±)‐(3a R, 4 S, 5 R, 10b S )‐5‐bromo‐7, 9‐dimethoxy‐4‐methyl‐4‐(4‐methylpent‐3‐en‐1‐yl)‐2‐(propan‐2‐ylidene)‐1, 2, 3, 3a, 4, 5‐hexahydro‐6 H ‐5, 10b‐methanobenzo[ e ]azulene‐6, 11‐dione} was found to inhibit the growth of Bacillus Calmette–Guérin (BCG)‐infected cells at concentrations similar to rifampicin. These results outperform the natural product, underscoring the potential of merochlorin analogues as a new class of antibiotics. Abstract : Antibiotic architecture : SAR studies of 16 derivatives of the structurally novel antibiotic merochlorin A, designed using a biosynthetic blueprint, were conducted. Our lead compounds are active against several Gram‐positive bacteria, and are relatively nontoxic to human cell lines.